2019
DOI: 10.3390/ijerph16142584
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor is Effective in the Treatment of Diabetic Foot Ulcers: Meta-Analysis and Systematic Review

Abstract: Diabetic foot ulcers (DFUs) are one the common complications of diabetes mellitus. Many trials were performed to evaluate the effect of recombinant human epidermal growth factor (rhEGF) in healing DFUs. This meta-analysis was performed to synthesize the evidence of rhEGF treatment in DFUs in comparison to placebo. Databases included for the search were PubMed, EMBASE, the Cochrane Library, Web of Science, EBSCOhost, ScienceDirect, and Scopus (up to January 2019). The outcome of interest was the complete healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…EGF is clinically approved in several countries for treating diabetic foot ulcers. Chronic wounds and their attendant consequences of severe pain, amputation, and disability remain an important health concern and an increasing socio-economic burden. , At least 15% of diabetic patients will develop chronic ulcers on their feet. The total medical cost for managing this ailment was estimated US$ 9–13 billion in the United States . In this regard, EGF, which plays important roles in proliferation, migration, and differentiation, offers promise as a therapeutic intervention for wound management .…”
Section: Introductionmentioning
confidence: 99%
“…EGF is clinically approved in several countries for treating diabetic foot ulcers. Chronic wounds and their attendant consequences of severe pain, amputation, and disability remain an important health concern and an increasing socio-economic burden. , At least 15% of diabetic patients will develop chronic ulcers on their feet. The total medical cost for managing this ailment was estimated US$ 9–13 billion in the United States . In this regard, EGF, which plays important roles in proliferation, migration, and differentiation, offers promise as a therapeutic intervention for wound management .…”
Section: Introductionmentioning
confidence: 99%
“…It can also correct the pseudo-healing of traumatic tympanic membrane perforations, after daily application over six months, to keep the membrane moist [80]. In patients with diabetic foot ulcers, parenteral administration of EGF on epithelial tissue has a positive effect on the healing process [81]. Dogan and colleagues conducted an experimental study performed on male Wistar-Albino rats divided into non-diabetic and diabetic rats and reported that EGF loaded in a gelatine-microsphere improves wound healing both in normal and diabetic rats [82].…”
Section: Epidermal Growth Factor and Wound Healingmentioning
confidence: 99%
“…32 The efficacy of rhEGF for the treatment of DFUs has been also confirmed in recent meta-analyses, but the quality of evidence was low. 31,33-35…”
Section: Adjunct Therapiesmentioning
confidence: 99%